Integral of cos^6(x) dx
The solution
Detail solution
-
Rewrite the integrand:
cos6(x)=(2cos(2x)+21)3
-
There are multiple ways to do this integral.
Method #1
-
Rewrite the integrand:
(2cos(2x)+21)3=8cos3(2x)+83cos2(2x)+83cos(2x)+81
-
Integrate term-by-term:
-
The integral of a constant times a function is the constant times the integral of the function:
∫8cos3(2x)dx=8∫cos3(2x)dx
-
Rewrite the integrand:
cos3(2x)=(1−sin2(2x))cos(2x)
-
There are multiple ways to do this integral.
Method #1
-
Let u=sin(2x).
Then let du=2cos(2x)dx and substitute du:
∫(21−2u2)du
-
Integrate term-by-term:
-
The integral of a constant is the constant times the variable of integration:
∫21du=2u
-
The integral of a constant times a function is the constant times the integral of the function:
∫(−2u2)du=−2∫u2du
-
The integral of un is n+1un+1 when n=−1:
∫u2du=3u3
So, the result is: −6u3
The result is: −6u3+2u
Now substitute u back in:
−6sin3(2x)+2sin(2x)
Method #2
-
Rewrite the integrand:
(1−sin2(2x))cos(2x)=−sin2(2x)cos(2x)+cos(2x)
-
Integrate term-by-term:
-
The integral of a constant times a function is the constant times the integral of the function:
∫(−sin2(2x)cos(2x))dx=−∫sin2(2x)cos(2x)dx
-
Let u=sin(2x).
Then let du=2cos(2x)dx and substitute 2du:
∫4u2du
-
The integral of a constant times a function is the constant times the integral of the function:
∫2u2du=2∫u2du
-
The integral of un is n+1un+1 when n=−1:
∫u2du=3u3
So, the result is: 6u3
Now substitute u back in:
6sin3(2x)
So, the result is: −6sin3(2x)
-
Let u=2x.
Then let du=2dx and substitute 2du:
∫4cos(u)du
-
The integral of a constant times a function is the constant times the integral of the function:
∫2cos(u)du=2∫cos(u)du
-
The integral of cosine is sine:
∫cos(u)du=sin(u)
So, the result is: 2sin(u)
Now substitute u back in:
2sin(2x)
The result is: −6sin3(2x)+2sin(2x)
Method #3
-
Rewrite the integrand:
(1−sin2(2x))cos(2x)=−sin2(2x)cos(2x)+cos(2x)
-
Integrate term-by-term:
-
The integral of a constant times a function is the constant times the integral of the function:
∫(−sin2(2x)cos(2x))dx=−∫sin2(2x)cos(2x)dx
-
Let u=sin(2x).
Then let du=2cos(2x)dx and substitute 2du:
∫4u2du
-
The integral of a constant times a function is the constant times the integral of the function:
∫2u2du=2∫u2du
-
The integral of un is n+1un+1 when n=−1:
∫u2du=3u3
So, the result is: 6u3
Now substitute u back in:
6sin3(2x)
So, the result is: −6sin3(2x)
-
Let u=2x.
Then let du=2dx and substitute 2du:
∫4cos(u)du
-
The integral of a constant times a function is the constant times the integral of the function:
∫2cos(u)du=2∫cos(u)du
-
The integral of cosine is sine:
∫cos(u)du=sin(u)
So, the result is: 2sin(u)
Now substitute u back in:
2sin(2x)
The result is: −6sin3(2x)+2sin(2x)
So, the result is: −48sin3(2x)+16sin(2x)
-
The integral of a constant times a function is the constant times the integral of the function:
∫83cos2(2x)dx=83∫cos2(2x)dx
-
Rewrite the integrand:
cos2(2x)=2cos(4x)+21
-
Integrate term-by-term:
-
The integral of a constant times a function is the constant times the integral of the function:
∫2cos(4x)dx=2∫cos(4x)dx
-
Let u=4x.
Then let du=4dx and substitute 4du:
∫16cos(u)du
-
The integral of a constant times a function is the constant times the integral of the function:
∫4cos(u)du=4∫cos(u)du
-
The integral of cosine is sine:
∫cos(u)du=sin(u)
So, the result is: 4sin(u)
Now substitute u back in:
4sin(4x)
So, the result is: 8sin(4x)
-
The integral of a constant is the constant times the variable of integration:
∫21dx=2x
The result is: 2x+8sin(4x)
So, the result is: 163x+643sin(4x)
-
The integral of a constant times a function is the constant times the integral of the function:
∫83cos(2x)dx=83∫cos(2x)dx
-
Let u=2x.
Then let du=2dx and substitute 2du:
∫4cos(u)du
-
The integral of a constant times a function is the constant times the integral of the function:
∫2cos(u)du=2∫cos(u)du
-
The integral of cosine is sine:
∫cos(u)du=sin(u)
So, the result is: 2sin(u)
Now substitute u back in:
2sin(2x)
So, the result is: 163sin(2x)
-
The integral of a constant is the constant times the variable of integration:
∫81dx=8x
The result is: 165x−48sin3(2x)+4sin(2x)+643sin(4x)
Method #2
-
Rewrite the integrand:
(2cos(2x)+21)3=8cos3(2x)+83cos2(2x)+83cos(2x)+81
-
Integrate term-by-term:
-
The integral of a constant times a function is the constant times the integral of the function:
∫8cos3(2x)dx=8∫cos3(2x)dx
-
Rewrite the integrand:
cos3(2x)=(1−sin2(2x))cos(2x)
-
Let u=sin(2x).
Then let du=2cos(2x)dx and substitute du:
∫(21−2u2)du
-
Integrate term-by-term:
-
The integral of a constant is the constant times the variable of integration:
∫21du=2u
-
The integral of a constant times a function is the constant times the integral of the function:
∫(−2u2)du=−2∫u2du
-
The integral of un is n+1un+1 when n=−1:
∫u2du=3u3
So, the result is: −6u3
The result is: −6u3+2u
Now substitute u back in:
−6sin3(2x)+2sin(2x)
So, the result is: −48sin3(2x)+16sin(2x)
-
The integral of a constant times a function is the constant times the integral of the function:
∫83cos2(2x)dx=83∫cos2(2x)dx
-
Rewrite the integrand:
cos2(2x)=2cos(4x)+21
-
Integrate term-by-term:
-
The integral of a constant times a function is the constant times the integral of the function:
∫2cos(4x)dx=2∫cos(4x)dx
-
Let u=4x.
Then let du=4dx and substitute 4du:
∫16cos(u)du
-
The integral of a constant times a function is the constant times the integral of the function:
∫4cos(u)du=4∫cos(u)du
-
The integral of cosine is sine:
∫cos(u)du=sin(u)
So, the result is: 4sin(u)
Now substitute u back in:
4sin(4x)
So, the result is: 8sin(4x)
-
The integral of a constant is the constant times the variable of integration:
∫21dx=2x
The result is: 2x+8sin(4x)
So, the result is: 163x+643sin(4x)
-
The integral of a constant times a function is the constant times the integral of the function:
∫83cos(2x)dx=83∫cos(2x)dx
-
Let u=2x.
Then let du=2dx and substitute 2du:
∫4cos(u)du
-
The integral of a constant times a function is the constant times the integral of the function:
∫2cos(u)du=2∫cos(u)du
-
The integral of cosine is sine:
∫cos(u)du=sin(u)
So, the result is: 2sin(u)
Now substitute u back in:
2sin(2x)
So, the result is: 163sin(2x)
-
The integral of a constant is the constant times the variable of integration:
∫81dx=8x
The result is: 165x−48sin3(2x)+4sin(2x)+643sin(4x)
-
Add the constant of integration:
165x−48sin3(2x)+4sin(2x)+643sin(4x)+constant
The answer is:
165x−48sin3(2x)+4sin(2x)+643sin(4x)+constant
The answer (Indefinite)
[src]
/
| 3
| 6 sin (2*x) sin(2*x) 3*sin(4*x) 5*x
| cos (x) dx = C - --------- + -------- + ---------- + ---
| 48 4 64 16
/
2163(2sin(4x)+2x)+8sin(2x)−3sin3(2x)+83sin(2x)+4x
The graph
5 3
5 cos (1)*sin(1) 5*cos(1)*sin(1) 5*cos (1)*sin(1)
-- + -------------- + --------------- + ----------------
16 6 16 24
1929sin4−4sin32+48sin2+60
=
5 3
5 cos (1)*sin(1) 5*cos(1)*sin(1) 5*cos (1)*sin(1)
-- + -------------- + --------------- + ----------------
16 6 16 24
6sin(1)cos5(1)+245sin(1)cos3(1)+165sin(1)cos(1)+165
Use the examples entering the upper and lower limits of integration.